ANALISIS TERHADAP PELUANG DAN TANTANGAN PERBANKAN SYARIAH DALAM ERA DIGITAL - Asriani, Asriani; Muhammad Iqbal fasa (Publikasi Inspirasi Indonesia, 2024)
Digital financial innovation (IKD) is a sign that the financial services sector is developing rapidly along with technology. Sharia banking is one of the organizers of IKD, so it is important for sharia banking to participate in the development of digital finance by presenting forms of IKD in sharia banking. The presence of IKD will certainly provide opportunities and charity. In this paper, a descriptive approach is used to conduct library research. First, the research results show that digital banking and its features are a form of digital financial innovation in sharia banking. Has been adjusted to POJK Number 13/POJK.02/2018. Apart from that, analysis of the use of IKD in sharia banking continues to increase every year. Apart from that, the research results show that sharia banking has many great opportunities in the current digital era. On the other hand, the most challenging banking problems in the current digital era are human resources, cyber security, consumer protection, and the public's low knowledge of sharia banking.